Quercetin manipulates the expression of genes involved in the reactive oxygen species (ROS) process in chicken heterophils - NAMBOOPPHA, Boondarika; PHOTICHAI, Kornravee; WONGSAWAN, Kanreuthai; CHUAMMITRI, Phongsakorn (Journal of Veterinary Medical Science, 2018)
Chicken heterophils generate reactive oxygen species (ROS) molecules to defend against invading pathogens. The present study examined effects of quercetin on chicken heterophils. Heterophils were stimulated with PBS, 50 µM quercetin (QH), PMA or Escherichia coli (EC) and the resulting intracellular ROS molecules were determined. Flow cytometry results showed that cells stimulated with QH, PMA and EC had a higher ROS production. Increases in intracellular ROS molecules were identified in all treatment groups by fluorescence microscopy. Determination of the ability of quercetin to manipulate mRNA expression of ROS subunits was assessed using real-time RT-PCR. Quercetin and other stimulants up-regulated the majority of genes involved in ROS production: CYBB (NOX2), NCF1 (p47phox), NCF2 (p67phox), NOX1 and RAC2. The antioxidant property of QH was explored by measuring mRNA expression of CAT and SOD1. The data indicate increased levels of CAT with all treatments; however, only QH attenuated the expression of the SOD1 gene. To further investigate the effects of ROS-driven inflammation or cell death, IL6, CASP8 and MCL1 genes were preferentially tested. The inflammatory gene (IL6) was profoundly down-regulated in the QH- and PMA-treated groups while EC induced a strikingly high IL6 expression level. Investigation of the known apoptotic (CASP8) and anti-apoptotic (MCL1) genes found down-regulation of CASP8 in the QH- and PMA-treated groups which were contradicted to the MCL1 gene. In conclusion, quercetin can enhance ROS production by regulating the expression of genes involved in ROS production as well as in subsequent processes.